Effect of caffeine on aerobic endurance performance - Itze Noriega Muro; Miguel Parada (Mexican Journal of Medical Research ICSA, 2016)
Supplementation in sport has become very important. The athlete uses ergogenic products or supplements such as caffeine, seeking to improve performance in sports. Therefore, the main objective of this study was to determine the effect of caffeine on aerobic endurance in Mexican professional soccer players. A longitudinal, experimental and prospective, crossover, double-blind, placebo-controlled study was conducted. Aerobic resistance was evaluated with the Yo-Yo Intermittent Recovery Test. Sixteen athletes were included, who were applied the Yo-Yo test before the administration of caffeine. With a crossover design, athletes received caffeine or placebo and the Yo-Yo test was applied. The initial heart rate (HR) of the athletes was 11.7 ± 93.2 (caffeine) and 94.4 ± 21.7 (placebo) (P = 0.85). The final HRs were of 175.8 ± 18.1 (caffeine) and 181.9 ± 13.0 (placebo) (P = 0.28). The HRs recovery were 141.4 ± 22.0 (caffeine) and 142.3 ± 24.4 (placebo) (P = 0.92) and a recovery rate of 34.4 ± 12.5 (caffeine) and 39.6 ± 19.3 (placebo) (P = 0.37). With a total of 2532.5 ± 267.6 meters traveled (caffeine) and 2622.5 ± 285.5 meters (placebo) (P = 0.36). Through the analysis of results, it is concluded that for this sample of athletes, caffeine supplementation had no positive influence on aerobic endurance.